Life Satisfaction and Religiosity among College Teachers - Jamal, Yousaf (Journal of Education and Vocational Research, 2014)
The present study aimed to explore the relationship between life satisfaction and religiosity among college teachers. Life satisfaction refers to cognitive and affective assessments of life. Religiosity refers to behavior, emotions, and thoughts which are derivative from beliefs about the sacred, associated with a particular religious ritual. A sample of 100 males and females college teachers was selected in a crosssectional survey research design. Muslim Religiosity Personality Inventory (MRPI) by Krauss (2011) and Satisfaction with Life Scale (SWLS) by Diener (1985) were used to measure the religiosity and life satisfaction respectively. Permissions to use the scales have already obtained from authors. Data were collected from a convenient sample of 100 college teachers from district Gujrat. Statistical Package for Social Sciences (SPSS) 20.0 version was used for statistical analyses. Findings of Pearson Product Moment Correlations revealed that life satisfaction is positively associated with religious rituals and maumalats at (p< .001 and p< .01 respectively). Multiple Hierarchal Regression Analysis showed that religious rituals and maumalats predict 29% variance on life satisfaction. The research has implementation that religiosity can play a vital role in life satisfaction of male and female college teachers.